Brazilian blood donation eligibility criteria for dermatologic patients Critérios brasileiros de elegibilidade à doação de sangue para pacientes dermatológicos - Carlos Gustavo Wambier; Caroline Silva Pereira; Benedito de Pina Almeida Prado Júnior; Norma Tiraboschi Foss (Sociedade Brasileira de Dermatologia, 2012)
A focused and commented review on the impact of dermatologic diseases and interventions in the solidary act of donating blood is presented to dermatologists to better advise their patients. This is a review of current Brazilian technical regulations on hemotherapeutic procedures as determined by Ministerial Directive #1353/2011 by the Ministry of Health and current internal regulations of the Hemotherapy Center of Ribeirão Preto, a regional reference center in hemotherapeutic procedures. Criteria for permanent inaptitude: autoimmune diseases (>1 organ involved), personal history of cancer other than basal cell carcinoma, severe atopic dermatitis or psoriasis, pemphigus foliaceus, porphyrias, filariasis, leprosy, extra pulmonary tuberculosis or paracoccidioidomycosis, and previous use of etretinate. Drugs that impose temporary ineligibility: other systemic retinoids, systemic corticosteroids, 5-alpha-reductase inhibitors, vaccines, methotrexate, beta-blockers, minoxidil, anti-epileptic, and anti-psychotic drugs. Other conditions that impose temporary ineligibility: occupational accident with biologic material, piercing, tattoo, sexually transmitted diseases, herpes, and bacterial infections, among others. Discussion: Thalidomide is currently missing in the teratogenic drugs list. Although finasteride was previously considered a drug that imposed permanent inaptitude, according to its short halflife current restriction of 1 month is still too long. Dermatologists should be able to advise their patients about proper timing to donate blood, and discuss the impact of drug withdrawal on treatment outcomes and to respect the designated washout periods. Uma revisão centrada no impacto de doenças e intervenções dermatológicas no ato solidário de doar sangue é apresentada aos dermatologistas para melhor aconselhamento dos seus pacientes. Esta é uma revisão das atuais normas técnicas brasileiras sobre procedimentos hemoterápicos conforme determinado pela Portaria Ministerial no 1353/2011 do Ministério da Saúde e atuais normas internas do Hemocentro de Ribeirão Preto, um centro de referência regional em procedimentos hemoterápicos. Critérios para inaptidão definitiva: doenças autoimunes (>1 órgão comprometido), antecedente pessoal de câncer diferente de carcinoma basocelular, dermatite atópica ou psoríase graves, pênfigo foliáceo, porfirias, filariose, hanseníase, tuberculose ou paracoccidioidomicose extrapulmonares e uso prévio de etretinato. São condições de inelegibilidade temporária: uso de outros retinóides sistêmicos, corticoides sistêmicos, inibidores da 5-alfa-redutase, vacinas, metotrexato, betabloqueadores, minoxidil, anticonvulsivantes e antipsicóticos. Outras condições responsáveis por inaptidão temporária: acidente ocupacional com material biológico, "piercing", tatuagem, doenças sexualmente transmissíveis, herpes, infecções bacterianas, entre outras. Discussão: Talidomida atualmente não consta na lista de medicações teratogênicas. Apesar do uso da finasterida já ter sido considerada como critério para inaptidão definitiva, de acordo com sua meia-vida curta a restrição atual de 1 mês ainda é demasiadamente longa. Dermatologistas devem ser capazes de aconselhar seus pacientes sobre o momento adequado para doar sangue e discutir o impacto da suspensão de medicações nos resultados do tratamento de forma a respeitar os períodos de restrição designados.